High-efficiency solar laser pumping by a ring-array concentrator - Matos, Rodrigo da Cunha Antunes Gomes de (2019)
Aiming to significantly improve solar laser efficiency, in this thesis, a 20 mm length 5.5 mm diameter Nd:YAG single-crystal rod can be efficiently pumped by highly concentrated solar radiation through a modified ring-array concentrator. Composed of six coaxial parabolic reflective rings and a small diameter Fresnel lens, the 1500 mm diameter modified ring-array concentrator can tightly focus incoming solar radiation into a 5.0 mm full width at half maximum focal spot. An innovative aspherical fused silica concentrator allows further pump light concentration into the Nd:YAG rod at the focal zone. A simple but effective water-cooling scheme within the aspherical concentrator constitutes another highlight of this assembly. Strong dependency of solar laser power on the rim angle of the ring-array concentrator was found through ZEMAX™ and LASCADTM analyses. A continuous-wave solar laser power of 67.8 W at 1064 nm and 38.4 W/m2 collection efficiency was numerically calculated, being 1.22 times more than the previous record. Also, 1.29, 1.03 and 1.85 times improvements in conversion, slope efficiencies and brightness figure of merit, respectively, were numerically achieved. The tracking error influence on solar laser output power was numerically calculated. A simple 1:7 scale model of the ring-array concentrator was also built to verify how the primary focusing performs in direct sunlight.